2018
DOI: 10.1021/acsami.8b16645
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Molecular Interaction of Human Dermal Fibroblasts with Bacterial Nanocellulose Composite Hydrogel for Tissue Regeneration

Abstract: The evaluation of the interaction of cells with biomaterials is fundamental to establish the suitability of the biomaterial for a specific application. In this study, the properties of bacterial nanocellulose/acrylic acid (BNC/AA) hydrogels fabricated with varying BNC to AA ratios and electron-beam irradiation doses were determined. The manner these hydrogel properties influence the behavior of human dermal fibroblasts (HDFs) at the cellular and molecular levels was also investigated, relating it to its applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 59 publications
4
27
0
Order By: Relevance
“…The fabricated Cur-loaded Cho/PEO/Col nanofibers showed a higher cell viability percentage compared with Col, Cho/PEO, and control sample on the third day. The obtained results confirmed the effective impact of cell–biomaterial interaction between fabricated nanofibers (with nanoscale fiber diameter, specific surface area, and high porosity) and HDF cells . Col nanofibers were introduced as a promising wound dressing in the wound-healing process.…”
Section: Discussionsupporting
confidence: 68%
“…The fabricated Cur-loaded Cho/PEO/Col nanofibers showed a higher cell viability percentage compared with Col, Cho/PEO, and control sample on the third day. The obtained results confirmed the effective impact of cell–biomaterial interaction between fabricated nanofibers (with nanoscale fiber diameter, specific surface area, and high porosity) and HDF cells . Col nanofibers were introduced as a promising wound dressing in the wound-healing process.…”
Section: Discussionsupporting
confidence: 68%
“…Furthermore, fatty acid component of NS such as oleic and linoleic acid maintain the water barrier and promote wound healing by selectively transferring in and out of the wound during the healing process [67]. Fatty acid activates neutrophil phagocytosis and releases cytokine and growth factors, leading to the improvement of wound healing [68,69].…”
Section: Discussionmentioning
confidence: 99%
“…Tissue engineering methods commonly utilize exogenous 3D extracellular matrices (ECMs) as scaffolds to accumulate cells in tissues, control tissue structure, and regulate cell phenotype . Recently, researchers reported that hydrogel-based bioactive scaffolds possess essential properties to become highly effective ECMs and have the potential to achieve cell adhesion and tissue proliferation . More specifically, hydrogel scaffolds play various important roles on tissue engineering, including space fillers, carriers of biologically active molecules, and 3D structures that act as tissue cells and induce stimuli to guide the formation of target tissues. , To date, different kind of natural polymers like proteins, hyaluronic acid and a variety of synthetic polymers include PVA, PAA and PAAm have been used in the preparation of tissue engineering scaffolds .…”
Section: Biomedical Application Of Bc-based Composite Scaffoldsmentioning
confidence: 99%